A Review of Endovascular Treatment for Posterior Circulation Strokes - Sung Hyun Baik; Jun Yup Kim; Cheolkyu Jung (Neurointervention, 2023)
Mechanical thrombectomy for acute posterior circulation strokes (PCSs) is recommended based on evidence from anterior circulation strokes (ACSs). Two recent randomized controlled trials showed that endovascular treatment (EVT) leads to better functional outcomes than those of the best medical care. However, many studies have shown that patients undergoing PC-EVT have a higher rate of futile recanalization than those undergoing AC-EVT. The characteristics and outcomes of PC-EVT may differ according to the pathological mechanisms, including cardioembolism, intracranial atherosclerosis, and tandem vertebrobasilar occlusion. We reviewed PC-EVT outcomes reported in recent studies and discussed technical considerations for maximizing treatment efficacy according to the etiology of a PCS.